Improving Eighth Graders’ Vocabulary Mastery through Students’ Learning Style-VARK-Based Flashcards - Nurhaliza; Valentina Dyah Arum Sari (English Language Education Department, Universitas Kristen Duta Wacana (UKDW), Yogyakarta, Indonesia, 2023)
Mastering vocabulary will help students in expressing their ideas or understanding others in an EFL context. However, it turns out that students have difficulty learning English due to a lack of vocabulary mastery. Therefore, the selection and the use of appropriate media were needed to help students achieve the learning objectives. In this study, the VARK questionnaire was distributed to students to see their learning styles. The results were that most of them are Read/Write type of learners. Considering that fact, students learning style VARK-based flashcards were implemented as a medium in this Classroom Action Research. This study aims to find out how flashcards can improve vocabulary mastery in class VIII C students of one state Junior High School in Teluk Keramat, Kalimantan. This study applied Classroom Action Research with 2 cycles with 33 student participants. The data analysis technique used mixed-method research; qualitative and quantitative. The instrument used questionnaires, interviews, observation checklists, and tests. The results indicated that students gained improvement after learning by using flashcards media. It was found that the average score of students in the pre-test was 34.9, post-test cycle I was 54.2, and post-test cycle II was 72.5. This proved that students' vocabulary mastery by using students' learning style VARK-based flashcards was improved. Further, it could be concluded that students learning style VARK-based flashcards gave a positive impact on the use of learning media in a Junior High School in Teluk Keramat to improve their vocabulary mastery.